Development of a remote physics laboratory to support equitable access to education - Ishafit Ishafit; Moh. Irma Sukarelawan; Toni Kus Indratno; Ariati Dina Puspitasari; Yoga Dwi Prabowo (International Journal of Evaluation and Research in Education (IJERE), 2025)
Economic disparities and variations in geographical conditions in Indonesia exacerbate access to physics laboratories. Therefore, innovative solutions such as remote physics laboratories are needed to bridge this gap and provide more equitable access to students across the region, regardless of economic or geographical conditions. To overcome this, this research aims to develop a remote physics laboratory for equitable access to quality physics experiments. This research includes 4D model development research. The research subjects involved five students for the functionality test, 84 people for the user test, and ten media experts to assess the feasibility of the product. The instruments used include functionality test instruments, media expert assessments, and usefulness, satisfaction, and ease of use (USE) questionnaires. Tool functionality data and media expert validation were analyzed using the Aiken V technique. At the same time, the level of user acceptance was examined through a combination of Wright maps and logit item values. This development resulted in a remote physics experiment architecture and device with a good functionality assessment index. The assessment by media experts showed high validity. The level of user acceptance is classified in the medium to high category. Thus, the developed R-PhyLab has the potential to be an effective medium in equalizing access to quality physics laboratories in educational institutions that face economic limitations and unfavorable geographical conditions.